2010
DOI: 10.1177/0266242610368592
|View full text |Cite
|
Sign up to set email alerts
|

Influence of work history on entrepreneurial intentions in ‘prime age’ and ‘third age’: A preliminary study

Abstract: This exploratory study investigates the relationship between an individual's socialization into different professional and organizational cultures and their subsequent entrepreneurial intentions. Using age cohorts as a proxy for the duration of work-related socialization processes and changes in the business environment over time, the study proposes that the impact of work history is stronger in 'third age' (50-64 years) than in 'prime age' (20-49 years). The principal finding is that older individuals, those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
148
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(166 citation statements)
references
References 46 publications
9
148
2
7
Order By: Relevance
“…In the same vein, some scholars focused on European countries. Kautonen et al (2010Kautonen et al ( , 2011 investigated grey entrepreneurship in Finland, Backman and Karlsson (2013) investigated the Swedish case and Curran and Blackburn (2001), Parker and Rougier (2007), Small (2012), and Kautonen (2013) investigated the phenomenon in the United Kingdom. Other scholars chose non-European countries.…”
Section: Methodology Data and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same vein, some scholars focused on European countries. Kautonen et al (2010Kautonen et al ( , 2011 investigated grey entrepreneurship in Finland, Backman and Karlsson (2013) investigated the Swedish case and Curran and Blackburn (2001), Parker and Rougier (2007), Small (2012), and Kautonen (2013) investigated the phenomenon in the United Kingdom. Other scholars chose non-European countries.…”
Section: Methodology Data and Resultsmentioning
confidence: 99%
“…This result is aligned with some previous studies. According to Kautonen et al (2010), some differences exist between young and third age entrepreneurs and, in particular, according to Zolin (2015), senior entrepreneurs display an exceptionally shrewd approach to entrepreneurship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, TPB has been found to be an effective model for studying and understanding entrepreneurial intention (Moriano et al, 2011;Van Gelderen et al, 2008). Using TPB to study entrepreneurial intention was found in various studies, for examples, Kautonen et al (2010), Sommer and Haug (2011), just to name a few. Thus, we decided to adapt TPB in determining the factors affecting the technical undergraduates' intention in becoming entrepreneurs.…”
Section: Proposed Entrepreneurial Intent Construct Among Technical Stmentioning
confidence: 99%
“…Both quantitative and qualitative studies have been exploited in order to describe and understand the phenomenon of older age entrepreneurship. Recent topics of older age entrepreneurship have covered such areas as older people attitudes to self-employment and factors influencing to self-employment (Curran & Blackburn, 2001); the influence of work history and age norms on entrepreneurial intentions in third age (Kautonen et al, 2010; ageing people motivations for business start-up (Kautonen, 2008); characteristics of early retirees as the next generation of entrepreneurs (Singh & DeNoble, 2003); the factors that affect grey entrepreneurs business behavior (Weber & Schaper, 2004) and institutional framework and factors influencing motives and incentives to be self-employed and/or start a business in older age (Kyrö, Moisala, & Nyrhinen, 2012).…”
mentioning
confidence: 99%